Event-based asynchronous dissipative filtering for T–S fuzzy singular Markovian jump systems with redundant channels. (November 2019) - Wang, Yanqian; Zhuang, Guangming; Chen, Fu
Abstract: In this paper, the issue of asynchronous dissipative filter design for a class of Takagi–Sugeno (T–S) fuzzy singular Markov jump systems (SMJSs) with redundant channels under the event-triggered scheme is investigated. The event-triggered scheme, the technique of redundant channels are adopted to relieve the total number of data transmission and improve the transmission quality over the network, respectively. The hidden Markov model (HMM) is utilized to describe the phenomena of asynchronous modes between the original system and the designed filter. Based on the stochastic Lyapunov functional and the method of free-weighting matrices, sufficient conditions of stochastically admissible and strictly dissipative for the filtering error system are developed concerning a set of linear matrix inequalities (LMIs). The co-design of asynchronous filter and the weighting matrices of the event-triggered scheme is determined by the feasible LMIs. Finally, a numerical example is presented to show the usefulness and effectiveness of the proposed method.